Problematics in Handling Criminal Offence on Poor Communities by Advocate (A Study on Gunung Sugih District Court) - Marwan Jaya Putra (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
The provision of legal aid to the poor is one of the actions of the noble profession of advocates and the moral movement that advocates for human rights, in fact, not all advocates are morally aware of their obligations. There are still many deviations found in the provision of legal aid for the poor. This condition is certainly contrary to the noble values of the advocate profession itself, in the presence of this matter, which shows still can be found deviations in practice. The problem examined in this study is why law enforcers such as judges and posbakum have not provided free legal assistance to the poor in Central Lampung Regency, a factor that has caused law enforcement agencies not to offer and provide free legal assistance to the poor and the pattern / model of handling criminal cases against the poor by advocates based on justice. The method used in this research is with socio-legal research approach that comes from collecting data obtained from primary data and secondary data, then analysed by qualitative analysis method.The results of this study ultimately provide an answer that Advocates who have not yet applied the value of justice in handling criminal cases involving the poor are due to legal substance, legal structure, and legal culture, Not yet applying the value of justice in handling criminal cases against the poor is like the emergence of mistrust of the law, besides the model of handling criminal cases against the poor by advocates based on the value of justice is the implementation of constructive strategies, such as: Legislation Planning, Policies and Activities Related to the Fulfilling Right to Legal Assistance. Suggestions from this research are to Advocates regarding Integrity, morality, idealism, and professionalism of law enforcement officers should be further enhanced, in addition to the restrictions on the provision of legal aid in LBH should also be reviewed to enforce the principle of providing legal assistance as widely and equality before the law.